2011
DOI: 10.1111/j.1742-4658.2011.08430.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific domains of nucleolin interact with Hdm2 and antagonize Hdm2‐mediated p53 ubiquitination

Abstract: Nucleolin is an abundant multifunctional nucleolar protein with defined roles in ribosomal RNA processing, RNA polymerase I-catalyzed transcription, and the regulation of apoptosis. Earlier we reported that human nucleolin binds to the p53-antagonist Hdm2 as determined by reciprocal co-immunoprecipitation assays using cell lysates. We also demonstrated that nucleolin antagonizes Hdm2-mediated degradation of p53. Here, we identify specific domains of nucleolin and Hdm2 proteins that support mutual interaction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…The nucleolus contains several kinds of NPs such as nucleolin and fibrillarin, which are known as the two major and multifunctional NPs, participating in rRNA processing and cell activities. They take key roles in rDNA transcripts and ribosome assembly (Sobol et al 2006, Ugrinova et al 2007, Tajrishi et al 2011, Bhatt et al 2012. As for what kind of NPs influenced by Cd, there are few reports concerning with them.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleolus contains several kinds of NPs such as nucleolin and fibrillarin, which are known as the two major and multifunctional NPs, participating in rRNA processing and cell activities. They take key roles in rDNA transcripts and ribosome assembly (Sobol et al 2006, Ugrinova et al 2007, Tajrishi et al 2011, Bhatt et al 2012. As for what kind of NPs influenced by Cd, there are few reports concerning with them.…”
Section: Discussionmentioning
confidence: 99%
“…However, domain-mapping experiments suggest that NCL binds p53 and HDM2 via different regionsthe C-terminal RGG domain and N-terminal RBD domains, respectively -and may form a ternary complex with both proteins simultaneously (Bhatt et al 2012). While NCL's interaction with HDM2 has been shown to inhibit HDM2-mediated p53 destabilization, both through driving p53-HDM2 dissociation and by promoting HDM2's own ubiquitination and degradation (Bhatt et al 2012;Saxena et al 2006), D r a f t 15 the formation of an NCL-p53-HDM2 ternary complex was also shown to result in recruitment of a ubiquitin protease, HAUSP, which supports deubiquitination and stabilization of p53, HDM2 and NCL (Lim et al 2015).…”
Section: Ncl Throughout the Cell -Nucleolus Nucleoplasm Cytoplasm Amentioning
confidence: 99%
“…While NCL's interaction with HDM2 has been shown to inhibit HDM2-mediated p53 destabilization, both through driving p53-HDM2 dissociation and by promoting HDM2's own ubiquitination and degradation (Bhatt et al 2012;Saxena et al 2006), D r a f t 15 the formation of an NCL-p53-HDM2 ternary complex was also shown to result in recruitment of a ubiquitin protease, HAUSP, which supports deubiquitination and stabilization of p53, HDM2 and NCL (Lim et al 2015). How these apparently contradictory pathways may be coordinated and/or interact to mediate NCL-dependent p53 stabilization remains to be fully dissected.…”
Section: Ncl Throughout the Cell -Nucleolus Nucleoplasm Cytoplasm Amentioning
confidence: 99%
See 2 more Smart Citations